False-Positive Phencyclidine (PCP) Result on 11-Panel Urine Drug Screen (UDS) in a 17-Year-Old Adolescent with Long-Term Venlafaxine Use - Kim, Hyun Sue; Jain, Aakash; Kablinger, Anita S. (Case Reports in Psychiatry, 2023)
Venlafaxine is an antidepressant belonging to the class of serotonin–norepinephrine reuptake inhibitors that are US Food and Drug Administration-approved to treat and manage symptoms of depression, anxiety, and other mood disorders in adults. We describe an adolescent patient who likely had a false-positive phencyclidine result detected with an 11-panel urine drug screen in an outpatient setting of long-term use of therapeutic venlafaxine extended release for the treatment of recurrent major depressive disorder and generalized anxiety disorder. We believe that this may be the first published case report to characterize this phenomenon in a young patient in the absence of an acute overdose.